Risk Factors for Severe Coronavirus Disease 2019 Among Human Immunodeficiency Virus-Infected and -Uninfected Individuals in South Africa, April 2020–March 2022: Data From Sentinel Surveillance. (2nd November 2022) - Walaza, Sibongile; Tempia, Stefano; von Gottberg, Anne; Wolter, Nicole; Bhiman, Jinal N; Buys, Amelia; Amoako, Daniel; Moosa, Fahima; du Plessis, Mignon; Moyes, Jocelyn; McMorrow, Meredith L; Dawood, Halima; et al.
Abstract: Background: Data on risk factors for coronavirus disease 2019 (COVID-19)-associated hospitalization and mortality in high human immunodeficiency virus (HIV) prevalence settings are limited. Methods: Using existing syndromic surveillance programs for influenza-like-illness and severe respiratory illness at sentinel sites in South Africa, we identified factors associated with COVID-19 hospitalization and mortality. Results: From April 2020 through March 2022, severe acute respiratory syndrome coronavirus 2 was detected in 24.0% (660 of 2746) of outpatient and 32.5% (2282 of 7025) of inpatient cases. Factors associated with COVID-19-associated hospitalization included the following: older age (25–44 [adjusted odds ratio aOR= 1.8, 95% confidence interval (CI) = 1.1–2.9], 45–64 [aOR = 6.8, 95% CI = 4.2–11.0] and ≥65 years [aOR = 26.6, 95% CI = 14.4–49.1] vs 15–24 years); black race (aOR, 3.3; 95% CI, 2.2–5.0); obesity (aOR, 2.3; 95% CI, 1.4–3.9); asthma (aOR, 3.5; 95% CI, 1.4–8.9); diabetes mellitus (aOR, 5.3; 95% CI, 3.1–9.3); HIV with CD4 ≥200/mm 3 (aOR, 1.5; 95% CI, 1.1–2.2) and CD4 <200/mm 3 (aOR, 10.5; 95% CI, 5.1–21.6) or tuberculosis (aOR, 12.8; 95% CI, 2.8–58.5). Infection with Beta (aOR, 0.5; 95% CI, .3–.7) vs Delta variant and being fully vaccinated (aOR, 0.1; 95% CI, .1–.3) were less associated with COVID-19 hospitalization. In-hospital mortality was increased in older age (45–64 years [aOR, 2.2; 95% CI, 1.6–3.2] and ≥65 years [aOR, 4.0; 95% CI, 2.8–5.8] vs 25–44 years) and male sex (aOR, 1.3; 95% CI, 1.0–1.6) and was lower in Omicron-infected (aOR, 0.3; 95% CI, .2–.6) vs Delta-infected individuals. Conclusions: Active syndromic surveillance encompassing clinical, laboratory, and genomic data identified setting-specific risk factors associated with COVID-19 severity that will inform prioritization of COVID-19 vaccine distribution. Elderly people with tuberculosis or people with HIV, especially severely immunosuppressed, should be prioritized for vaccination. Abstract : Omicron variant was associated with reduced risk of mortality and Beta associated with decreased risk of hospitalization. Syndromic surveillance can be used to describe epidemic timing, epidemiological characteristics of cases, early detection of variants, and how these impact disease severity/outcomes.